Communication Clashes Between Autistic Children and Parents in Non-Verbal Behavior - Rahayu, Astira Putri; Ramadhana, Maulana Rezi; Priastuty, Chairunnisa Widya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Communication within a family will indirectly create harmony and a close bond between parents and children. However, not all families can realize harmony. This is because there is a family given a particular child or a child with special needs, one of which is a child with autism. The purpose of this study is to understand the interpersonal relationship between parents and children with autism who have limitations in communication using the Relational Dialectics Theory (RDT) approach. This research applied a qualitative research method with a descriptive approach. The research results indicated that the relational dialectics of interpersonal relationships between parents and children with autism raise tension or tension when building communication. Of course, this will challenge parents to address tension when building communication with children with autism to create communication that can be understood by each other.